Nonreciprocal scattering and unidirectional cloaking in nonlinear nanoantennas - Goh Heedong; Krasnok Alex; Alù Andrea (Nanophotonics)
Reciprocal scatterers necessarily extinguish the same amount of incoming power when excited from opposite directions. This property implies that it is not possible to realize scatterers that are transparent when excited from one direction but that scatter and absorb light for the opposite excitation, limiting opportunities in the context of asymmetric imaging and nanophotonic circuits. This reciprocity constraint may be overcome with an external bias that breaks time-reversal symmetry, posing however challenges in terms of practical implementations and integration. Here, we explore the use of tailored nonlinearities combined with geometric asymmetries in suitably tailored resonant nanoantennas. We demonstrate that, under suitable design conditions, a nonlinear scatterer can be cloaked for one excitation direction, yet strongly scatters when excited at the same frequency and intensity from the opposite direction. This nonreciprocal scattering phenomenon opens opportunities for nonlinear nanophotonics, asymmetric imaging and visibility, all-optical signal processing and directional sensing.